Financial Constraints: Do They Matter to Allocate R&D Subsidies? - Silva, Filipe (2017)
We examine whether subsidies are allocated to financially constrained firms and if they effectively alleviate these constraints. We claim that in addition to the usual “public good” arguments behind the allocation of subsidies, the extent to which firms are able to obtain external funding should not be overlooked. Overall, our results question both the allocation and the effectiveness of subsidies in alleviating financial constraints of firms willing to innovate. Additionally, the decision criteria for allocating public funds seem to be similar from those used by the private investors. These results have important implications on the design of future innovation policy.